NEGASI DALAM BAHASA INDONESIA DAN BAHASA INGGRIS - Dian Noviani Syafar (Masyarakat Linguistik Indonesia Universitas Andalas, 2016)
This study is entitled Negation in Indonesia and English. Traditionally, people differentiate positive and negative sentences by identifying